TARGETING ACADEMIC SURGEONS RESTORING THE DIGNITY OF SURGICAL EDUCATION-TRAINING IN INDONESIA: A MODEL OF EXCELLENCE IN PROFESSIONAL ACHIEVEMENT - Lalisang, Toar Jean Maurice (Universitas Gadjah Mada, 2023)
Background: Due to the dynamic changes in the strategic environment and development of science and technology, the Indonesian national education system has undergone various adjustments, including surgeons' education training programs. To some extent, various essential changes, marginalization, and pragmatization of surgical services have degraded the dignity of surgical education-training programs in Indonesia. This study aims to analyse several causal factors appropriately to direct to an appropriate target based on the present and future situation to prevent inappropriate solutions.Methods: This narrative review is based on related articles freely downloaded, which discuss the what and why of uncertainty in the provision of education-training today and suggest how changes must be made to restore the dignity of Surgeons in Indonesia. Current Indonesian conditions are mainly based on implementation at the Surgery Department, Medicine of Faculty Universitas Indonesia and Cipto Mangunkusumo Hospital.Results: It is challenging to obtain data on evaluating the educational process and the quality of surgeon graduates. Based on observation, there are four main problems, including the recruitment of teaching staff, Ministry of Education and Culture policies, adequateness of learning materials, and the phenomenon of semester-based graduation. These problems lead to quasi-referral and case management of defensive surgery, which gradually declines the surgeon profession's dignity.Conclusion: The fundamental solution to restoring the dignity of surgeons in Indonesia is to provide an education-training which produce academic surgeons.